Language and culture virtual exchanges in higher education: A case study - María Victoria Guadamillas Gómez (Universidad de Guadalajara, 2017)
This study describes a teaching intervention carried out in the field of telecollaboration on a university-level course. Two main goals were set for this didactic innovation, which was carried out through an Interinstitutional Teaching Project: firstly, to increase the time of exposure to the foreign language (English/Spanish) and secondly, to raise cultural awareness among British and Spanish university students. The qualitative method has been applied in order to describe the participation and involvement of the learners. This case study firstly describes telecollaboration and the research that has recently been carried out in this field. Secondly, it presents the three phases of the project: action plan, development and evaluation. Thirdly, participants' perceptions (both positive and negative) are described. Students' comments are analyzed mainly in terms of linguistic, cultural or other general features expressed by participants. Finally, this case study includes a conclusion in which planning strategies and task design are emphasized, since both have brought about a successful experience for university students.